2020
DOI: 10.2147/ijn.s233663
|View full text |Cite
|
Sign up to set email alerts
|

<p>Filter-Membrane-Based Ultrafiltration Coupled with Surface-Enhanced Raman Spectroscopy for Potential Differentiation of Benign and Malignant Thyroid Tumors from Blood Plasma</p>

Abstract: The objective of this study is to evaluate the performance and feasibility of surface-enhanced Raman spectroscopy coupled with a filter membrane and advanced multivariate data analysis on identifying and differentiating benign and malignant thyroid tumors from blood plasma. Patients and Methods: We proposed a membrane filter SERS technology for the differentiation between benign thyroid tumor and thyroid cancer. That is to say, by using filter membranes with optimal pore size, the blood plasma samples from thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Diagnostic sensitivities of 89% and 86%, and corresponding specificities of 71% and 79%, were achieved, using either 785 or 633 nm, respectively. Liang et al [81] employed SERS for differentiation of benign (n ¼ 30) and malignant (n ¼ 70) thyroid tumors from blood plasma which had been subjected to ultrafiltration, resulting in 90% discrimination accuracy.…”
Section: Head and Neck Cancersmentioning
confidence: 99%
“…Diagnostic sensitivities of 89% and 86%, and corresponding specificities of 71% and 79%, were achieved, using either 785 or 633 nm, respectively. Liang et al [81] employed SERS for differentiation of benign (n ¼ 30) and malignant (n ¼ 70) thyroid tumors from blood plasma which had been subjected to ultrafiltration, resulting in 90% discrimination accuracy.…”
Section: Head and Neck Cancersmentioning
confidence: 99%
“…Nevertheless, over the past few years, the metabolomics approach in terms of thyroid diagnosis has shown an enormous evolution, which is due, in part, to the application of several analytical techniques that allow the study of the complete set of small biomolecules that make up a biological sample. The main metabolomics techniques that have mostly been adopted in the thyroid, in an attempt to identify biomarkers, classify the thyroid cancer, facilitate an earlier diagnosis and prevent the development and invasion at the systemic level of the cancer itself, are Mass Spectrometry (MS) [53][54][55], Nuclear Magnetic Resonance (NMR) [53,56,57], Raman Spectroscopy [58][59][60] and Fourier Transform Infrared (FTIR) Spectroscopy [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. This increase in the number of studies is attributed to the greater availability of improved and accurate metabolomics techniques that exist and also due to the development of appropriate statistical tools that are able to handle the huge amount of data resulting from the samples under analysis [80].…”
Section: New Diagnostic Approach-metabolomics Techniquesmentioning
confidence: 99%
“…In particular, label-free SERS, which can directly detect bioanalytes after adsorption onto a nanostructured gold or silver surface, is a convenient and cost-effective approach that, in contrast to label-based SERS strategies, does not require complicated sample preparation or expensive Raman tags [ 13 , 14 ]. Recently, label-free blood SERS analysis has blossomed into an area of intensive research for cancer diagnosis, and it has been shown to be of significant clinical value for nasopharyngeal [ 15 ], gastric [ 16 ], thyroid [ 17 ], prostate [ 18 ], lung [ 19 ], and breast cancers [ 20 ]. A label-free blood SERS method for NPC detection has also been applied by our group to analyze and identify the different tumor (T) stages.…”
Section: Introductionmentioning
confidence: 99%